2023
DOI: 10.3389/fimmu.2022.1071204
|View full text |Cite|
|
Sign up to set email alerts
|

SARS-CoV-2 antibody response after mRNA vaccination in healthcare workers with and without previous COVID-19, a follow-up study from the University Hospital in Krakow, Poland

Abstract: IntroductionHealthcare workers (HCWs) from the beginning of the pandemic have been at risk of exposure to SARS-CoV-2, so they were vaccinated as first.ObjectivesThe purpose of the study was to determine the level of antibodies against SARS-CoV-2 in HCWs before and after vaccination with mRNA preparations according to previous COVID- 19.Patients and methodsThe HCWs from the University Hospital in Krakow completed two surveys: the baseline survey before receiving the first dose of vaccine (in January 2021) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…In our study group, IgG class anti-SARS-CoV-2 antibody levels were significantly lower among people who had previously had COVID-19 than among those who received COVID-19 vaccination, which is consistent with the reports of other researchers [50]. This confirms the high immunogenicity of vaccines against COVID-19 reported in the Polish population in other studies [51] for the immune response evoked by the vaccine and the magnitude of the response sustained over time [52].…”
Section: Discussionsupporting
confidence: 92%
“…In our study group, IgG class anti-SARS-CoV-2 antibody levels were significantly lower among people who had previously had COVID-19 than among those who received COVID-19 vaccination, which is consistent with the reports of other researchers [50]. This confirms the high immunogenicity of vaccines against COVID-19 reported in the Polish population in other studies [51] for the immune response evoked by the vaccine and the magnitude of the response sustained over time [52].…”
Section: Discussionsupporting
confidence: 92%
“…Healthcare workers are definitely a priority group for vaccination against COVID-19 [ 8 ]. Therefore, healthcare workers were vaccinated first, in order to protect the vulnerable part of the population and frontline employees and to stop the spread of the virus and the spread of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, nowadays, when COVID-19 has become a constant companion in our daily lives, vaccination is an irreplaceable means of preventing this epidemic [ 7 ]. Studies revealed the effectiveness of vaccination against COVID-19 and also after getting infected with SARS-CoV-2 in healthcare employees [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is limited data on the incidence of SARS-CoV-2 infection among HCWs beyond the second wave of the pandemic, and limited data on the incidence of infection before and after the implementation of the vaccination programme, especially for European countries [ 10 ]. So far, most studies performed in Poland were voluntary seroprevalence studies, so the representativeness of the results obtained may be limited [ 11 , 12 ]. Knowing the factors associated with SARS-CoV-2 infection in HCWs informs preventive measures and improves the protection of HCWs and patients.…”
Section: Introductionmentioning
confidence: 99%